Calculate the derivative of (x^2-5)^4 - (x^2-5)^3

Expert Answers
justaguide eNotes educator| Certified Educator

We have to find the derivative of: (x^2-5)^4 - (x^2-5)^3

y = (x^2-5)^4 - (x^2-5)^3

use the chain rule to find the derivative

y' = [(x^2-5)^4 - (x^2-5)^3]'

=> [(x^2-5)^4]' - [(x^2-5)^3]'

=> 4(x^2 - 5)^3*2x - 3(x^2 - 5)^2*2x

=> 8x(x^2 - 5)^3 - 6x(x^2 - 5)^2

The required derivative is: 8x(x^2 - 5)^3 - 6x(x^2 - 5)^2

schwarzhand | Student

y' = [(x^2-5)^4 - (x^2-5)^3]'

=> [(x^2-5)^4]' - [(x^2-5)^3]'

=> 4(x^2 - 5)^3*2x - 3(x^2 - 5)^2*2x

=> 8x(x^2 - 5)^3 - 6x(x^2 - 5)^2

like that

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question